Challenges and Benefits of Working in Teams – Interpersonal Interactions in Health Care - Bányai, G.; Bíró, K. (International Journal of Engineering and Management Sciences, 2017)
Teamwork has become the accepted way of doing one’s job. This is so true even profession’s that were considered an exception are shifting towards teamwork. Apart from the well-known benefits, there seems to be a downside of the enforcement of this work strategy. Conflicts, frictions, frustration in working groups can affect the dignity, psychological or physical integrity of team members, generally referred to as psychological harassment, workplace bullying or mobbing. The outcomes of the phenomenon are various negative organizational responses. Health care is somewhat lagging behind in this shift towards working in teams, but with increasing specialization greater coordination is needed between health care professionals. Above all, the patient wishes to be more involved in the health care process. Research suggests that patient involvement and working in teams have a positive impact on effectiveness and patient mortality, respectively. One of the challenges for health care is to include the patient in the teamwork process as an equal member of the group and at the same time overcome the drawbacks mentioned above, in a setting where a traditional, paternalistic approach is still present and the vulnerability of the patient (and his/her dignity) is evident.